ANALISIS PENGARUH NON PERFORMING LOAN, LOAN TO DEPOSIT RATIO, DAN CAPITAL ADEQUACY RATIO TERHADAP RETURN ON ASSETS PADA BANK BUMN DI INDONESIA - Sari, Dyah Novita; Sriwidodo, Untung; Indriastuti, Dorothea Ririn (Universitas Slamet Riyadi, 2018)
This study aims to determine the effect of variable Non-Performing Loans (NPL), Loan to Deposit Ratio (LDR), and Capital Adequacy Ratio (CAR) on Return on Assets in BUMN Banks in Indonesia. The type of research used in this study is quantitative research. This study uses the entire population, namely state-owned banks in Indonesia. The type of data used in this study is secondary data. Data obtained from the annual financial statements for the 2013 – 2017 period at the BUMN Bank, namely PT. Bank Negara Indonesia (Persero) Tbk, PT. Bank Rakyat Indonesia (Persero) Tbk, PT. State Savings Bank (Persero) Tbk, and PT. Bank Mandiri (Persero) Tbk, which was published on the Indonesia Stock Exchange. The data analysis technique used in this study is multiple linear regression analysis. The results of the t-test research show that NPL has a significant effect on ROA, LDR has a significant effect on ROA, while CAR has no significant effect on ROA. F test results show that NPL, LDR, and CAR simultaneously have a significant effect on ROAKeywords: NPL, LDR, CAR, ROA